TINGKAT KEMANDIRIAN PESERTA DIDIK SETELAH MENDAPATKAN LAYANAN KONSELING PERORANGAN DI SMA NEGERI 1 DUA KOTO KABUPATEN PASAMAN (StudiDeskriptifAnalitisPadaSemuaPesertaDidikyang TelahMendapatkanLayananKonselingPerorangan di SMA Negeri I Dua Koto Kabupa - Fauzan, Fauzan; Kasih, Fitria; Nita, Rahma Wira (Bimbingan dan Konseling, 2013)
This research describe levels of students independencegot individual counseling inSenior High School 1 Duo Koto KabupatenPasaman. Research purpose is: 1).Todescribe levels of self-conscious to studentsâ independent gotindividual counseling2). To describelevels of studentsâindependencecarefully gotindividual counseling3). To describe levels of independence, studentsâ individualitygotindividual counseling 4). To describelevels of independent toward studentâs independence gotindividual counseling.This descriptive research that took all students for population who followed individual counseling. This use purposive random sampling and percentage formula toÂ  data analysis. Research results can be described Â like: 1). Levels of Studentsâ independence got individual counseling in high category can be seen from level of self-conscious from percentage 68.3%.2). Levels of Studentsâ independence gotindividual counseling in high category can be seen from levels closely from percentage67,14% 3). Levels of Studentsâ independence gotindividual counseling in high categorycan be seen from level of individuality from percentage 63,79%. 4). Levels of Studentsâ independence gotindividual counseling in high categorycan be seen from level of self from percentage 68,46%. Fromresearch result, researcher suggest for supervising teacher tostreamline individual counseling to achieve level of independenceintact.